Nickel biosorption by finely ground waste sludge - Hannachi, Yasser (Journal of Environmental Engineering and Landscape Management, 2011)
In this paper, removal of Ni (II) from aqueous solution by finely ground waste sludge (FGWS) was investigated. Waste sludge samples obtained from a varnishes and lacquers industry wastewater treatment plant was dried, ground and pre-treated with 1% H2O2 to improve the biosorption capacity. Kinetics of nickel biosorption onto FGWS was investigated by using the FGWS samples with particle size of 62.2 µm. The pseudo-first and second order rate expressions were used to correlate the experimental data. The kinetic constants were determined for both models and the second order rate expression was found to be more suitable. Three different biosorption isotherms were used to correlate the equilibrium biosorption data and the isotherm constants were determined. The Langmuir isotherm was found to fit the experimental data better than the other tested isotherms. The biosorption capacity (qm) and saturation constant (K) for the Langmuir isotherm showed that finely ground waste sludge has the largest capacity and affinity for removal of Ni(II) compared to the other Activated sludges. Article in English. Биосорбция никеля мелко измельченным илом стоков Santrauka. Nagrinėjami Ni(II) šalinimo iš vandeninių tirpalų smulkiai sumaltu nuotekų dumblu (SSND) tyrimų rezultatai. Nuotekų dumblo pavyzdžiai imti iš glazūravimo ir lakavimo pramonės nuotekų valymo įrenginių, išdžiovinti, susmulkinti ir apdoroti 1% H2O2, kad padidėtų biosorbcijos tūris. Nikelio sorbcijos SSND kinetika tirta naudojant SSND bandinius, kurių dalelių dydis 62,2 µm. Pseudo pirmojo ir antrojo laipsnio greičio išraiškos buvo taikomos eksperimentinių duomenų koreliacijai apibrėžti. Kinetinė konstanta nustatyta abiejų modelių, tačiau antrojo laipsnio greičio išraiška buvo tinkamesnė. Pagal tris skirtingas biosorbcijos izotermes nustatyta biosorbcijos pusiausvyros duomenų koreliacija, rastos izotermių konstantos. Langmiuro (Langmuir) izotermė geriau atitiko eksperimentinius duomenis nei kitos tirtosios izotermės. Pagal Langmiuro izotermę biosorbcijos geba (q m) ir prisotinimo konstanta (K) rodė, kad smulkiai sumalto nuotekų dumblo geba šalinti Ni(II) yra didžiausia, palyginti su kitos rūšies aktyvintojo dumblo. Reikšminiai žodžiai: biosorbcijos geba, smulkiai sumaltas nuotekų dumblas, antrojo laipsnio greitis, nikelio(II) jonai, Langmiuro (Langmuir) izotermė. Nikelio biosorbavimas smulkiai sumaltu nuotekų dumblu Резюме. Исследуется удаление Ni(II) из водных растворов мелко измельченным илом стоков (МИИС). Образцы ила стоковбыли взяты из оборудования по очистке стоков в промышленности по глазурованию и лакованию. Затем образцы были высушены, измельчены и обработаны 1-процентным H2O2, с целью увеличить объем биосорбции. Кинетика сорбции никеля МИИС исследовалась с применением образцов МИИС, величина частиц которых составляла62,2 μм. Выражения скорости псевдопервой и псевдовторой степени использовались для определения корреляции экспериментальных данных. Кинетическая константа была установлена для обеих моделей. Однако выражение скорости второй степени оказалось более приемлемым. Три разные изотермы биосорбции применялись для определения корреляции данных по равновесию биосорбции и констант изотерм. Изотерма Langmuir лучше совпала с экспериментальными данными, чем другие испытуемые изотермы. Способность биосорбции (q m) изотермы Langmuir и константа насыщения (K) показали, что мелко измельченный ил стоков обладает наибольшей способностью удалять Ni(II) по сравнению с другими видами активированного ила. Ключевые слова: способность биосорбции, мелко измельченный ил стоков, скорость второй степени, ионы никеля (II), изотерма Langmuir.